THE (IN) EFFICIENCY OF WORKER PROTECTION NETWORK AND ITS CHALLENGES IN ADDRESSING TRAFFICKING AND CONTEMPORARY SLAVERY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
More than 130 years after the promulgation of the Golden Law, a legal diploma that extinguished slavery in Brazil in 1888, it is necessary to study this phenomenon that has transcended in time and still causes thousands of victims at present. Despite all the technological advancement, the evolution of the means of production, it still worries everyone about the existence of this practice, given the transformations of capital, labor and production relations that have occurred over the last centuries. Modern slavery is not only characterized by forced labor, but has taken on new forms, encompassing various violations, such as the exploitation of child labor, debt servitude, domestic servitude, servile marriages, sexual slavery, and human trafficking. In this context, the research will investigate, through an exploratory bibliographic review, based on the doctrine, jurisprudence and international norms, the challenges to be overcome by the Brazilian State, flanked by international organizations, in the struggle in defense of human rights, as well as what were the ensured achievements over time for the effective eradication of human trafficking and modern slavery.